Some Relationships Between Evolutionary Stability Criteria in Games - Martin Dufwenberg (Uppsala University, Department of Economics, 1996)
The relationships between five stability criteria for evolutionary games are studies.
urn:nbn:se:uu:diva-2374
Keywords: C72; 330; Noncooperative games